МЕТОДИКА ОБУЧЕНИЯ ЛИНГВИСТИЧЕСКОЙ ТЕРМИНОЛОГИИ КАК СРЕДСТВО РАЗВИТИЯ ПРОФЕССИОНАЛЬНОЙ КОМПЕТЕНЦИИ БУДУЩИХ ФИЛОЛОГОВ - Худжамова Хуснора Диёр кизи (Innovate Conferences, 2025)
odern requirements for training philologists are determined not only by the need to master foreign languages, cultural knowledge, and text analysis skills, but also by the ability to use linguistic terminology as a primary means of professional communication. Terminology in linguistics is not simply a set of specialized words, but an entire system of concepts reflecting scientific understanding of language, its structure, functions, and development.